Apheresis of Deceased Donors as a New Source of Mobilized Peripheral Blood Hematopoietic Stem Cells for Transplant Tolerance. Issue 2 (17th August 2022) - Sosa, Rebecca A.; Mone, Thomas; Naini, Bita V.; Kohn, Donald B.; Reed, Elaine F.; Wheeler, Kristina; Campo-Fernandez, Beatriz; Davila, Alejandra; Chaffin, Donald J.; DiNorcia, Joseph; Kaldas, Fady M.; Cohen, Aaron; et al.
Abstract : Background: Solid organ transplantation is the therapy of choice for many patients with end-stage organ failure; however, recipients must remain on lifelong immunosuppression, leaving them susceptible to infections and cancer. The study of transplant tolerance to prolong graft survival in the absence of immunosuppression has been restricted to recipients of living donor allografts; however, deceased donors significantly outnumber living donors. Mobilization of hematopoietic stem cells (HSCs) from the bone marrow to peripheral blood (PB) could allow PB-HSCs to be used to induce tolerance in deceased donor kidney recipients; however, a major concern is the well-known concomitant mobilization of immune cells into the liver. Methods: We mobilized HSCs to the PD using a protocol of 2 doses of granulocyte colony-stimulating factor and 1 dose of plerixafor, followed by the collection of mobilized cells via apheresis in 3 deceased donors. The physiological, laboratory, and radiographic parameters were monitored throughout the procedure. Longitudinal biopsies were performed to assess the potential for ectopic liver mobilization. Results: The use of both agents led to the successful mobilization of peripheral blood CD34+ cells, demonstrating the potential for use in transplant tolerance protocols. Increased immune cell trafficking into the liver was not observed, and apheresis of mobilized cells resulted in a uniform decrease in all liver leukocyte subsets. Conclusions: HSCs can be mobilized and collected from the PB of brain-dead donors. This new approach may facilitate the dissemination of immune tolerance trials beyond living-donor kidney transplantation to deceased-donor transplantation, without sacrificing the transplantability of the liver. Abstract :